Dados linguísticos e iniciativa Linking Open Data - Botácio, Andrieli Cristina (Universidade Federal de São Carlos, 2020)
Tim Berners-Lee proposed the Semantic Web for better information retrieval. In this context, there are the Linked Data principles through which the data connection on the Web is established which the main objective is to generate meaning to the Web pages. And, by utilizing, this causes with which the software agents and people could cooperate with each other to reach their goals in an efficient manner. The project consists of working with an initiative that is an example of the application of Linked Open Data, which is the Linking Open Data (LOD), which brings data published in linked data format. The research will focus on describing and analyzing the linguistic datasets present in this initiative. From this point, it is incited as a research problem: what is identified in the links and linguistic datasets in the Linking Open Data initiative? Focusing on this problem, the objective is to map the datasets corresponding to the ‘Linguistics’ category inserted in the Linking Open Data initiative. It is an exploratory and qualitative research and of a theoretical-applied nature, addressing as main theme the mapping of linguistic datasets in Linking Open Data. First, a theoretical and practical investigation was carried out on the identification of the linguistic data sets and the technologies used in the connection of these data; after the investigation was directed to the analysis of the Linguistics category of the Linking Open Data initiative. The results obtained show that types of datasets and technologies of the Semantic Web are found in each of the seven categories of linguistic data: Corpora; Lexicons and Dictionaries; Terminologies, Thesauri and Knowledge Bases; Linguistic Resource Metadata; Linguistic Data Categories; Typological Databases; Other. It is concluded that the Linking Open Data initiative satisfactorily fulfills its function, showing the viability of the open data connection, through the prescribed technologies. As for the linguistic data of such an initiative, it is noted that they are extremely relevant and employs the technologies according required in each category.
Linguistic data and Linking Open Data initiative
Keywords: Web Semântica; Linked Open Data; Dados linguísticos; Linked data; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::TECNICAS DE RECUPERACAO DE INFORMACAO